Analisis Formalistik Lukisan Djoko Pekik Berjudul "Pawang Pun Kesurupan" - Syai'in, Ahmad; Prasetyo, Abdul Rahman (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
Djoko Pekik has an expressive realist painting style. He often embellishes populist values in almost every painting. Many of his works contain social criticism and political tragedies. That is why his paintings are so influential. Starting his painting career in 1958 by entering ASRI Yogyakarta, Djoko Pekik continued to revolutionise himself until now his name is well known in the art world. He even founded Sanggar Bumi Tarung in 1961 with a number of his friends. The collective art idea was later known to be affiliated with the People's Cultural Institute (Lekra). The purpose of formalistic criticism is to describe the configuration of formal aspects and noble values related to the elements of painting formation. The target of art criticism will be more inclined to the visual elements consisting of colour, line, and texture. The art criticism method used is formalistic criticism with description stages, formal analysis stages, interpretation stages, and evaluation stages. The results of this formalistic criticism are in the form of visual analysis data of paintings and interpretations of noble values related to the elements of the formation of paintings.